Stratigraphy and U – Pb zircon geochronology of Kidd Creek: implications for the formation of giant volcanogenic massive sulphide deposits and the tectonic history of the Abitibi greenstone belt - Bleeker, Wouter; Parrish, Randall R. (Canadian Journal of Earth Sciences, 1996)
Within the context of a structural–stratigraphic analysis of the giant Kidd Creek Cu–Zn–Ag deposit, precise U–Pb zircon ages have been obtained for five critical rock units associated with the deposit. Massive, flow-banded footwall rhyolite is dated at 2714.3 ± 1.2 Ma, slightly younger than a previously published age of 2717 ± 2 Ma on nearby rhyolite breccia. Extrusive rhyolite in the immediate hanging wall to the main ore lenses is dated at 2711.5 ± 1.2 Ma, leaving an interval of one to several million years for the formation of the deposit. We consider the demonstrated longevity of the Kidd Creek hydrothermal system as a major control on its giant size. Age constraints together with the size of the deposit suggest a time-averaged rate of base-metal sulphide deposition of about 10–100 t/year. Peak rates were likely one to possibly two orders of magnitude above time-averaged rates, hence 100–1000 t/year or higher. Detrital zircon ages on greywackes in the structural footwall to the deposit support structural observations that the metasediments are unrelated and significantly younger than the volcanics that host the deposit. All greywackes near Kidd Creek are younger than 2699 Ma and should be included in the Porcupine Group, which is redefined to include "Keewatin-age" greywacke turbidites that overlie the Krist Fragmental unit, but are themselves overlain by polymict conglomerates at the base of the Timiskaming sequence. The Prosser Porphyry, a quartz–plagioclase-porphyritic granitoid stock northeast of Kidd Creek, is dated at [Formula: see text] Ma, supporting structural observations that it is not a synvolcanic intrusion.